PENINGKATAN ADDED VALUE KOPRA PUTIH DENGAN METODA INDIRECT DRYING - M Imron Mustajib; Burhan Burhan (AGROINTEK, 2014)
Traditionally, drying of copra is carried out by sundrying or fumigation on a tomang (clay furnace). However, using these methods, the quality of copra resulted cannot be guaranteed and the prices is low, and thus the process is unprofitable. Another problem is that it is difficult to do the process during rainy season. We facilitated a copra home industry with a dryer with indirect drying system to replace the old copra processing drying equipment. The dryer consists of 12 racks equipped with a temperature controller (with temperatures reaching 150 ° C) and a timer. By controlling temperature and time it was possible to get good quality copra and the process can be done in rainy season. From the test results using LPG fuel at temperature of 70 ° C for 18 hours, white copra was produced with 7% moisture content.